Uncertainty, exchange rate regimes, and national price levels - Christian Broda (Federal Reserve Bank of New York, 2002)
Large differences in national price levels exist across countries. In this paper, I develop a general equilibrium model predicting that these differences should be related to countries' exchange rate regimes. My empirical findings confirm that countries with fixed exchange rate regimes have higher national price levels than countries with flexible regimes. At the disaggregate level, the relationship between exchange rate regimes and national price levels is stronger for nontraded goods than for traded goods. I also find that measuring the misalignment in national price levels around times of regime shifts without considering a break in its equilibrium value results in the overestimation of the true misalignment.
Keywords: E52; F33; F41; 330; Preisniveau; Internationaler Preiszusammenhang; Wechselkurssystem; Handelbares Gut; Nicht-handelbares Gut; Allgemeines Gleichgewicht; Schätzung; Welt